EVALUATING THE SERVICE QUALITY OF INTERNATIONAL BUSINESS ADMINISTRATION USING IMPORTANCE AND PERFORMANCE ANALYSIS - Tumewu, Arantxa Clara (Sam Ratulangi University, 2016)
Service Quality offered by Higher Education Institution is one of the most important aspects that become the reason students and parents choose higher education institutions such as University for continuing education. Therefore, to be competitive, the University must improve the service quality to be able to achieve the expectations of the students. This study aims to analyze how important the service quality and how the performance of International Business Administration’ service quality by using Importance and Performance Analysis.60 active International Business Administration students were sampled using purposive sampling technique. The results showed that the number of classes and facilities, cleanliness and comfort of IBA and the quality of the lecturers are three attributes that are very important and also the performance institutions is high, while the other attributes there is a very important but the performance is low, is not important but the performance is high, but nonecistent attribute located in quadrant unimportant and low performance. From the results, the researchers suggest IBA management to focus and allocate resources of attributes that are not important to attribute more important.